Stock market reactions to US Consumer Product Safety Commission enforcement actions - Ameer R; Othman R (John Wiley and Sons Australia, Ltd on behalf of Accounting and Finance Association of Australia and New Zealand., 2023)
This study examines stock market reaction to violations of product safety regulations and firm product responsibilities in the post-enforcement period. Our event study results show that market reaction was negative to failures by firms to report product defects in a timely way. Our results also show that the stock market reaction varies depending on the type of violations, and whether there are single or multiple violations. Firms spend more on research and development and advertising in the post-enforcement period, in addition to investing in their compliance programmes which have a significant positive impact on product responsibility stewardship. Our empirical results show that the stock market reacts negatively to recall volume and refund remediation strategy. The stock market reaction is negative to social media communication about product recalls initiated by manufacturers. However, this negative effect appears to be counteracted by the positive corporate social responsibility (CSR) reputation effect of the manufacturers. Our findings imply that US manufacturing firms dealing with product recalls must be sensitive to how consumers and investors interpret the communication.
Keywords: Consumer Product Safety Commission; consumer protection; enforcement; market valuation; product responsibility